Chemical composition of bird cherry fruits in the Northwestern region of Russia - S. Yu. Orlova; A. A. Yushev; T. V. Shelenga (Труды по прикладной ботанике, генетике и селекции)
Background. Among stone fruit plants, a special place belongs to bird cherry (Padus Mill.). As a food plant, it has found use in areas with harsh climate conditions. Since the breeding of bird cherry cultivars for food purposes continues to develop, there is a need to know the chemical composition of its fruits. The aim of this research was to study bird cherry in the environments of the Russian Northwest and isolate genotypes with an optimal biochemical composition for subsequent use.Materials and methods. Fruit composition in 21 accessions from the bird cherry collection was analyzed in 2009 and 2011–2013 at the Biochemistry and Molecular Biology Laboratory of the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR). Biochemical studies were performed using the methods adopted at VIR. Statistical processing of the data obtained was made using the Microsoft Excel software package.Results. The best genotypes were selected for each chemical component: for increased soluble solid content (SSC), accessions of Group I ‘Nevesta’ (29.63%), 1-1-8 (30.35), ‘Carpaty 5’ (30.87), ‘Chaika’ (33.9); for accumulation of sugars, ‘Granatovaya grozd’ (Group III; 12.13%), 1-1-8 (Gr. I; 12.5), ‘Pamyati Salamatova’ (Gr. IV; 12.8); for low acid content, ‘Sibirskaya krasavitsa’ (Gr. II; 1.03%), 1-1-8 (Gr. I; 1.14) ‘Granatovaya grozd’ (Gr. III; 1.17), ‘Zelenoplodnaya’ (Gr. I; 1.21), ‘Pozdnyaya radost’ (Gr. III; 1.25); for high content of ascorbic acid, 1-1-8 (Gr. I; 19.1 mg/100 g), ‘Sakhalinskaya chernaya’ (Gr. I; 19.35) ‘Rannyaya kruglaya’ (Gr. IV; 20.65), ‘Krasny shater’ (Gr. II; 21.23); for triterpene (ursolic, oleanolic) acids, ‘Cherny blesk’ (Gr. IV; 0.045%) and ‘Atica’ (Gr. I; 0.056).Conclusion. Significant differences were found in SSC between accessions of Groups I (P. avium) and II (P. avium × P. virginiana); and in the sugar/acid ratio (SAR), between I (P. avium) and IV (seedlings of cv. ‘Pamyati Salamatova’); II (P. avium × P. virginiana) and III (P. virginiana × P. avium); III (P. virginiana × P. avium) and IV (seedlings of cv. ‘Pamyati Sala matova’).